Efficiency improvement of passively cooled micro-scale hybrid CPV-TEG systems at ultra-high concentration levels. (15th September 2021) - Valera, Álvaro; Rodrigo, Pedro M.; Almonacid, Florencia; Fernández, Eduardo F.
Highlights: Thermoelectric-concentrator photovoltaics at ultra-high concentration is analysed. 3D finite-element methodology is implemented for concentrations up to 4, 000 suns. The influence of the key design parameters of the hybrid receiver is assessed. The hybridization could achieve relative efficiency improvement of 10.8 %. Abstract: Concentrator photovoltaic technology faces the challenge of evolving toward ultra-high concentration levels (>2, 000 suns) to increase the conversion efficiency of sunlight to electricity and lower the system cost. Recent studies have analysed technical issues related to optics, concentrator solar cell development, and thermal management. On the contrary, the hybridisation of thermoelectric generators with concentrator systems is a promising way to recover part of the waste heat generated in the solar cells and convert it to electricity, thereby enhancing global efficiency. There is theoretical evidence that increasing the concentration factor favours this type of hybridisation. However, the investigation of hybrid thermoelectric concentrator photovoltaic systems at ultra-high concentration levels is pending. In this study, a detailed 3D finite-element approach, which is also validated with previous literature, is used to analyse the efficiency improvement achievable with these hybrid systems at concentration factors of up to 4, 000 suns using passive cooling. The use of micro-scale solar cells reduces the thermal requirements, making the use of passive cooling mechanisms feasible. The influence of a number of design parameters (such as solar cell area, temperature coefficient of efficiency, area ratio, thermoelectric leg height, fill factor, and ZT figure-of-merit or heat-exchanger thermal resistance) in the system thermal and electrical performance was assessed. With this information, a future optimum hybrid solar receiver is numerically evaluated assuming that several technological constraints present in the state-of-the-art concentrator receivers are overcome, i.e. that microcells of 0.5 × 0.5 mm 2 at 4, 000 suns operating at 150 °C with extremely low-temperature coefficient of efficiency and very low heat-exchanger thermal resistance can be manufactured in next years. The results demonstrate that the use of thermoelectric generators with a high ZT could improve the efficiency of a concentrator photovoltaic-only receiver using the same solar cell at the same concentration up to 10.8% in relative magnitude. This study should encourage researchers to solve the problems associated with ultra-high concentrations of micro-scale high-temperature multi-junction solar cells integrated with high-efficiency optics, high ZT thermoelectric materials, and powerful cooling mechanisms.